PENGEMBANGAN MEDIA MINIATUR 3D PADA MATERI SISTEM TATA SURYA SISWAQKELAS VI SEKOLAH DASAR - Dwinata, Anggara; Aka, Kukuh Andri; Falah, Fajrul (Jurnal Kajian Pembelajaran dan Keilmuan, 2023)
This study attempts to produce media miniature learning solar system 3d to the matter solar system. Media developed by following the 10 steps of research. However, this study is limited to the stage of the revision of the final product. This type of research is research development commonly called R amp; D (Research and Development) by following the procedures of the Borg and Gall. The subject is used as the sample research is grade VI. Stages of research covering the stages of product development media, stages the validation material experts, media experts, practitioners, and trial stages of the product. Product test stage consists of three phases, namely the stage of limited trials or individual trials subject to the number of 3 students. Stages of small-group test with a test subject of 6 students. The operational test phase with the number of the subject test as many as 35 students. Data analysis technique used is descriptive qualitative as well as quantitative. The results of the study the development of this indicates that the media miniature the solar system 3d fit for use as a medium of learning .As well as meet the criteria kevalidan , practicality , and based on the effectiveness of validation of the team media experts , expert matter , and practitioners , as well as passing the trial of the product.